DEVELOPMENT OF SETS-BASED CHEMISTRY LEARNING E-MODULES (SCIENCE, ENVIRONMENT, TECHNOLOGY, SOCIETY) ON COLLIGATIVE PROPERTIES OF SOLUTIONS - Rahmawati Maharni; Burhanudin Milama; Rizqy Nur Sholihat (EDUSAINS, 2021)
DEVELOPMENT OF SETS-BASED CHEMISTRY LEARNING E-MODULES (SCIENCE, ENVIRONMENT, TECHNOLOGY, SOCIETY) ON COLLIGATIVE PROPERTIES OF SOLUTIONSAbstractThis study aims to produce an e-module for learning chemistry based on SETS (Science, Environment, Technology, Society) on the colligative properties of solutions, and to find out students' responses to the e-module. This study uses a 4-D model (define, design, development, and disseminate) which is limited only to the development stage. The instruments used in this research are needs analysis questionnaire, student analysis questionnaire, module content validation sheet, and student response questionnaire sheet. The validation of the content of the module was carried out by 2 instructional review experts and 1 practitioner. Based on the validator's assessment, a valid and worthy module was produced to be tested. The e-module trial phase was carried out on 35 students of class XII MIPA at SMAN 4, South Tangerang City. Based on the student response questionnaire, obtained a percentage of 82.5% in the SETS-based learning aspect which is included in the very good category. Overall, there was a positive response to the developed e-module with an average percentage of 82.93% which was included in the very good category and was suitable for use as a medium and source of learning in the learning process.AbstrakPenelitian ini bertujuan untuk menghasilkan e-modul pembelajaran kimia berbasis SETS (Science, Environment, Technology, Society) pada materi sifat koligatif larutan, serta mengetahui tanggapan siswa terhadap e-modul tersebut. Penelitian ini menggunakan model 4-D (define, design, development, dan disseminate) yang dibatasi hanya sampai tahap development. Instrumen yang digunakan dalam penelitian ini yaitu angket analisi kebutuhan, angket analisis peserta didik, lembar validasi isi modul, dan lembar angket respon siswa. Validasi isi modul dilakukan oleh 2 orang ahli kajian instruksional dan 1 orang praktisi. Berdasarkan penilaian validator, dihasilkan modul yang valid dan layak untuk diuji coba. Tahap uji coba e-modul dilakukan terhadap 35 orang siswa kelas XII MIPA di SMAN 4 Kota Tangerang Selatan. Berdasarkan angket respon siswa, diperoleh presentase sebesar 82,5% pada aspek pembelajaran berbasis SETS yang termasuk kedalam kategori sangat baik. Secara keseluruhan, diperoleh respon positif terhadap e-modul yang dikembangkan dengan presentase rata-rata sebesar 82,93% yang termasuk dalam kategori sangat baik dan layak digunakan sebagai media dan sumber belajar dalam proses pembelajaran.